Hubungan Body Image Dengan Kepercayaan Diri Pada Korban Body Shaming Pengguna Instagram - Agus Kurniawan; IGAA Noviekayati; Amherstia Pasca Rina (Universitas Muhammadiyah Gresik, 2023)
This study was conducted with the aim of knowing the correlation between body image and self-confidence in victims of body shaming, especially Instagram users. The method used in this study uses quantitative methods by distributing questionnaires, which consist of 2 (two) variables, namely the self-confidence variable (Y) and the body image variable (X). Respondents in this study were teenagers to adults aged 18-25 years who experienced body shaming as many as 134 respondents. The sampling technique used in this study is purpose sampling where the sample is taken by adjusting to certain criteria. Based on calculations using the spearman's rho non-parametric correlation technique with the IBM SPSS 24 for windows program. The results obtained are rxy 0.362 with a significance value of p = 0.000 where p <0.05. That is, the higher the body image, the higher the self-confidence of adolescent Instagram users, so the research hypothesis